RANCANG BANGUN SISTEM PEMESANAN TIKET TRAVEL BERBASIS WEBSITE PADA PT. RSIMA PEKANBARU - Arribe, Edo; Wahyu, Nova; Salsabilah, Annisa Eka (JURNAL ILMIAH INFORMATIKA, 2024)
RSIMA TRAVEL Pekanbaru, located on Jl. Unggas in Pekanbaru, Riau, currently still uses a manual ticket booking system. The current way of working creates difficulties for passengers in accessing departure schedules, which makes them have to come directly to the location or use the telephone. To overcome this challenge, switching to a computerized system is a must. The need for a computerized system is emphasized by the potential to simplify the process, make it faster, and more accurate compared to a manual system. This research aims to develop a ticket booking system that not only improves the efficiency of the booking process, but also provides easily accessible and informative data for passengers. Along with that, this research also aims to reduce the managerial burden associated with booking reports for travel company owners.The research method used in this research is descriptive, with system development using the Prototype method. Data is obtained through interviews, observations, and literature studies. MySQL is used as the database foundation for the PT. RSIMA TRAVEL Pekanbaru ticketing system, which is developed using the Laravel programming language.The result of this research is an information system that can facilitate administrators and passengers in transacting and getting information about PT. RSIMA TRAVEL Pekanbaru. The existence of this computerized solution is expected to.